anonymous
  • anonymous
What is the range of the graph of y = (x - 4)^2 + 3
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
jim_thompson5910
  • jim_thompson5910
Hint: In general, the range of y = a(x-h)^2+k is [k, infinity) if a > 0
anonymous
  • anonymous
Y ≤ 3??
jim_thompson5910
  • jim_thompson5910
close, it should be \[\Large y \ge 3\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
What about this.... 4x^2 + 13x = -3
jim_thompson5910
  • jim_thompson5910
You need to complete the square. Do you know how do to that?
anonymous
  • anonymous
no
anonymous
  • anonymous
So the answer would be x = -1/4 and x = -3
jim_thompson5910
  • jim_thompson5910
you're looking for the range correct?
anonymous
  • anonymous
No just solving the equation
jim_thompson5910
  • jim_thompson5910
oh sry, I thought you were finding the range
jim_thompson5910
  • jim_thompson5910
4x^2 + 13x = -3 4x^2 + 13x + 3 = 0 Now use the quadratic formula to solve for x x = (-b+-sqrt(b^2-4ac))/(2a) x = (-(13)+-sqrt((13)^2-4(4)(3)))/(2(4)) x = (-13+-sqrt(169-(48)))/(8) x = (-13+-sqrt(121))/8 x = (-13+sqrt(121))/8 or x = (-13-sqrt(121))/8 x = (-13+11)/8 or x = (-13-11)/8 x = -2/8 or x = -24/8 x = -1/4 or x = -3 So you are correct, nice job
anonymous
  • anonymous
Thank you thank you! :)
jim_thompson5910
  • jim_thompson5910
sure thing

Looking for something else?

Not the answer you are looking for? Search for more explanations.